Parents' perspectives on their children's music therapy: A synthesis of qualitative literature. (May 2020) - Annesley, Luke; McKeown, Eamonn; Curtis-Tyler, Katherine
There is no existing qualitative synthesis of the music therapy literature on parents' perspectives on their children's music therapy. This study seeks to fill this gap, motivated by the first author's experiences as a clinician/researcher. A systematic search of health databases, hand searches of key journals and searches of doctoral theses were undertaken to identify relevant studies. Thirteen studies which met inclusion criteria, including a total of 102 participants, were identified. Relevant data were extracted from these studies for comparison and analysis, with quality of studies assessed using the CASP appraisal tool. Findings were analysed following procedures of thematic synthesis. Six descriptive themes were grouped into three analytic themes: Parents perceived positive impacts of music therapy on their children; parents experienced music therapy as a nurturing environment for themselves and their children ; and some parents experienced challenges to their engagement with music therapy . Most studies (12/13) explored parents' perceptions of music therapy where they were included in sessions. The findings identify positive perceptions of family-centred models of music therapy for children and parents. Parents' perceptions of children were altered positively through experiencing them in new ways in music therapy. Parents also perceived positive outcomes for their children. These findings identify an emphasis in the qualitative literature on parents' perceptions on research into music therapy which includes parents in sessions. Only one study explored perceptions of a model where parents were not present during their child's sessions. More research is needed into parents' perceptions of music therapy where parents are not present during sessions. Further intervention studies into family-centred models of music therapy with children are also recommended.